Prediction of genetic potential of ornamental pepper parents - Albuquerque, Alejandra Semiramis; Silva Freitas , Gabriel; Gloria Marcelino, Reginaldo Arthur (Comunicata Scientiae, 2021)
Parental choice is very important in breeding programs. Better results are obtained when in the base population, a large genetic variability is combined with high average for traits. The objective was to estimate averages, heritabilities and genetic diversity among eight Capsicum annuum ornamental lines based on fruit and plant characteristics and to determine the correlation between these traits and their contribution to genetic variability in order to predict the potential of these accessions as genitors. Data were subjected to analysis of variance and means were grouped by Scott- Knott method at 5% probability. Estimates of heritabilities and genetic (CVg) and environmental (CVe) variances were obtained. Tocher's and canonical variables analysis were used to evaluate genetic divergence. The importance of variables for estimating genetic divergence was determined by the Singh’s method, by canonical analysis and based on genotypic correlations. CVg/CVe ratio indicated greater importance of genetic variation in relation to environmental variation. Heritabilities ranged from 70% to 99.87%. Due to genotypic correlations, selection to increase the number of fruits leads to desirable increases in canopy diameter, leaf length and width and to undesirable increases in plant height and days for flowering and fruiting. Based on averages and on Tocher’s and canonical variables methods, crossings between UFSJ 7 and UFSJ 4, UFSJ 5 and UFSJ 6 were recommended. Dry matter fruit content and days for flowering contributed least to genetic divergence, and should be suppressed in future works, and leaf length and width contributed most to this estimate.